Petrology of the Permian-Triassic granitoids in Northwest Vietnam and their relation to the amalgamation of the Indochina and Sino-Vietnam composite terranes - Tran Tuan, Anh; Tran Trong, Hoa; Pham Ngoc, Can; Gregory Shellnutt, J.; Pham T., Thuy; Izokh E., Andrey; Pham Thi Phuong, Lien; Duangpaseuth, Somsanith; Soulintone, Oneta (Vietnam Journal of Earth Sciences, 2022)
Granitoids from seven massifs in northwest Vietnam, including I-type granites (Nam Meng, Nam Rom, and Song Ma massifs) and S-type granites (Pu Si Lung, Kim Boi, Muong Lat, and Sam Son massifs) that distributed along the Dien Bien-Song Ma fault at the northern part of Truong Son Fold Belt, were studied to understand the mineralogy, whole-rock geochemistry, Nd-Sr isotopes, and U-Pb zircon geochronology. The I-type granitoid rocks vary from gabbro diorite to diorite and granodiorite to granite (SiO2 = 52.4 - 71.1 wt.%) and from calc-alkaline to high K calc-alkaline to shoshonite (Nam Rom massif) series. Biotite in the I-type granitoid rocks has high Mg, intermediate to high Ti, and low Al (Phl-0.43 - Sid-0.29 - Ann-0.28); amphibole is edenite (Nam Rom massif) and ferro-edenite (Song Ma massif). The ASI varies from 0.64 to 1.14 (metaluminous); K/Na = 0.1-0.7; ratios of K/Rb, Rb/Sr and Rb/Ba varies from 179-334, 0.40-3.50, and 0.16-0.38; [La/Sm]N, [La/Yb]N and [Gd/Yb]N are varies within 1.08-4.92, 1.57-27.3, and 1.07-3.72, respectively. Their 87Sr/86Sr and ƐNd(t) are highly enriched, respectively, from 0.7072 to 0.7319 and -12.2 to -6.67. The I-type granitoid rocks may be mixtures between mantle-derived and crustal components based on geochemical characteristics. In contrast, the Nam Meng magma was mantle-dominated, and the Nam Rom and Song Ma magmas were crustal-dominated. The S-type granitoid rocks include biotite granite and two-mica granite (SiO2 = 68.9-73.0 wt.%), varying from high K calc-alkaline to shoshonite series. The S-type granitoid rocks are distinct from the I-type granitoid rocks by sillimanite, cordierite, and muscovite. Biotite in the S-type granitoid rocks has high Ti and Al and low Mg. The mineral was partially replaced by muscovite. The ASI varies from 1.1 to 1.85 (peraluminous); K/Rb, Rb/Sr, and Rb/Ba vary within 161-188, 0.37-3.50, and 0.15-0.98; [La/Sm]N, [La/Yb]N and [Gd/Yb]N vary within 2.28-3.90, 5.93-16.8, and 1.72-2.93, respectively. The S-type granitoid rocks also have high 87Sr/86Sr(i) (0.7227-0.7335) and low ƐNd(t) (-12.4 to -9.8) with TDM = 2.11-2.71 billion years, indicating a mature crust protolith. The in situ zircon U-Pb ages of the I-type granites are 289-296 Ma (Nam Meng massif) and 245-225 Ma (Nam Rom and Song Ma massifs), while those of the S-type granitoid rocks (Kim Boi and Muong Lat massifs) are 242-235 Ma. The above data suggest that the Indochina and Sino-Vietnam composite terranes produced the Permian-Triassic granitoid rocks in northwest Vietnam. The convergence had led to subduction activity forming Nam Meng granitoid, syn-collision activity forming Kim Boi, Muong Lat, and Sam Son massifs, and ended with post-collision activity forming Nam Rom and Song Ma massifs.